Back Cover: On the Influence of the Protonation States of Active Site Residues on AChE Reactivation: A QM/MM Approach (ChemBioChem 7/2017). (20th March 2017) - Driant, Thomas; Nachon, Florian; Ollivier, Cyril; Renard, Pierre‐Yves; Derat, Etienne
Abstract : The back cover picture shows how, through a combination of calculations mixing quantum and molecular mechanics (as depicted by the code), the reactivation process of acetylcholinesterase inhibited by nerve agent can be better understood (enzyme shown as a ribbon). In particular, simulations demonstrate that an active‐site glutamate is able to deprotonate the α‐nucleophiles commonly used to reactivate this enzyme (stylized movie with arrows illustrating proton transfer). As the active site of serine hydrolases, such as acetylcholinesterase, is highly conserved, this work gives insights into the interplay between the catalytic triad and this basic glutamate. This project was funded by the French DoD.